Clinicopathological Spectrum of Thyroid Swelling — A Study at MonnoMedical College and Hospital in Bangladesh (The Planet, 2024)
Introduction: The thyroid gland is essential for metabolic regulation and endocrine function. Thyroid swelling, or goiter, can present with various clinical manifestations and pathological features. The clinicopathological spectrum of thyroid swellings includes benign conditions like multinodular goiter and thyroiditis, as well as malignant disorders such as thyroid carcinomas. This study aimed to explore the wide-ranging clinical and pathological aspects of thyroid swellings. Methods & Materials: This prospective study was conducted in the Department of ENT & HNS, Monno Medical College and Hospital, Manikganj, Bangladesh from January, 2019 to December, 2023. For this study, 90 resected specimens from thyroid surgeries were enrolled as subjects. A purposive sampling technique was utilized for sample selection. Data analysis was conducted using MS Office tools. Results: Clinically, 54.4% and as per ultrasonography, 78.9% of cases had solid consistency of swelling; 90.0% of the cases were euthyroid. The left lobe was involved in 45.5% of cases, and the right lobe in 42.5%. As per the fine needle aspiration cytology of thyroid nodules, 43.3% were benign, and 5.6% were malignant cases. Conclusion: Among thyroid swelling cases, solid consistency is very common. The involvement of the right and left lobes occurs with nearly equal frequency, accounting for nearly half of the cases. In approximately 5% of these cases, malignancy may be found.
Keywords: Clinicopathological spectrum; Thyroid swelling; Solid; Euthyroid; Colloid goiter; malignancy